IDX Food and Beverage Companies Financial Reporting Timelines: Do Profitability, Auditor Opinion, and Company Size Play a Role? - de-Olivera, Claudine (Indonesian Journal of Sustainability Policy and Technology, 2024)
This study aims to analyze the effect of profitability, auditor's opinion, and company size on the timeliness of financial report submissions in companies listed on the Indonesia Stock Exchange (IDX) from 2021-2023. The financial report submission timeline is one of the important components in information disclosure that can influence investment decisions and market confidence. Profitability is measured using Return on Assets (ROA), the auditor's opinion is seen based on the type of audit opinion given, and company size is measured from total assets. This study uses a quantitative method with a multiple regression approach. The research sample consisted of 12 Food and Beverage companies listed on the IDX during the period studied, which were selected using a purposive sampling technique. Secondary data from financial reports and company audit opinions were taken from the official IDX website and the company's annual report. The results of the study indicate that profitability and company size have a positive and significant effect on financial report submission timeliness, while the auditor's opinion does not have a significant effect. This finding indicates that larger and more profitable companies tend to be timelier in reporting their finances, while the type of auditor's opinion is not a determining factor in terms of timeliness. This study contributes to the literature on financial reporting in the Indonesian capital market and provides recommendations for companies and regulators to pay more attention to internal factors that influence financial report timeliness.